Strategi Pemasaran Tanaman Hias “Bunga Ditepi Jalan” Di Kelurahan Winangun Satu Kecamatan Malalayang Kota Manado - Paendong, Eunike Louisa; Porajow, Oktavianus; Benu, Noortje Marselianie (Sam Ratulangi University, 2023)
The aim of this research is to find out what factors exist in the internal and external environment and to determine the right marketing strategy for the